One piece : Skypeia, 28-29-30 - Oda, Eiichirō, 1975-; Forbes, Jake; Bates, Megan (Shonen jump manga., 2014)
Luffy and the Straw Hats clash mightily on the sky island of Skypiea with a wannabe deity named Kami Eneru. Kami's got an arsenal of thunderously destructive weapons at the ready, but the Straw Hats are just as determined to win the battle. At stake is a bounty of gold beyond the pirates' wildest imagination.